2013
DOI: 10.5194/angeo-31-1597-2013
|View full text |Cite
|
Sign up to set email alerts
|

Changes in the ultra-low frequency wave field during the precursor phase to the Sichuan earthquake: DEMETER observations

Abstract: Abstract. Electromagnetic phenomena observed in association with increases in seismic activity have been studied for several decades. These phenomena are generated during the precursory phases of an earthquake as well as during the main event. Their occurrence during the precursory phases may be used in short-term prediction of a large earthquake. In this paper, we examine ultra-low frequency (ULF) electric field data from the DEMETER satellite during the period leading up to the Sichuan earthquake. It is show… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
1
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(27 citation statements)
references
References 19 publications
(14 reference statements)
0
27
0
Order By: Relevance
“…Many researchers have also performed investigations on seismo-ionospheric effects since the occurrence of the Wenchuan M S 8.0 EQ. These studies include at least ionospheric changes of ground-based ionosonde data [57][58][59][60][61][62][63][64], DEMETER satellite data [17,[65][66][67][68][69][70][71][72][73][74][75][76][77][78], ground-based GPS satellite data [17,28,57,58,74,77,[79][80][81][82][83][84], radio occultation data from six microsatellites of FORMOSAT3/COSMIC (F3/C) data [81,84,85], and CHAMP (challenging minisatellite payload) satellite data [77].…”
Section: Spatial Ionospheric Anomaliesmentioning
confidence: 99%
“…Many researchers have also performed investigations on seismo-ionospheric effects since the occurrence of the Wenchuan M S 8.0 EQ. These studies include at least ionospheric changes of ground-based ionosonde data [57][58][59][60][61][62][63][64], DEMETER satellite data [17,[65][66][67][68][69][70][71][72][73][74][75][76][77][78], ground-based GPS satellite data [17,28,57,58,74,77,[79][80][81][82][83][84], radio occultation data from six microsatellites of FORMOSAT3/COSMIC (F3/C) data [81,84,85], and CHAMP (challenging minisatellite payload) satellite data [77].…”
Section: Spatial Ionospheric Anomaliesmentioning
confidence: 99%
“…Since the Wenchuan large earthquake in May 2008, a number of papers have been published that describe the precursory increase of the total electron content (TEC) related to the earthquake [ Zhao et al , ; Pulinets et al , ; Klimenko et al , ]. Walker et al [] reported that an increase in ULF wave activity was found in the vicinity of the epicenter of the Wenchuan earthquake. Therefore, the ionospheric disturbances related to the Wenchuan earthquake of May 2008 have been revisited through investigating the N e and O + densities, the electric field data of DEMETER [ Parrot , ], and the N e of CHAMP [ Lühr et al , ], in addition to the global VTEC data provided by the International GNSS (Global Navigation Satellite Systems) Service (IGS) [ Hernández‐Pajares et al , ].…”
Section: Introductionmentioning
confidence: 99%
“…However, we have succeeded in identifying the depression of ULF horizontal magnetic field as the signature of lower ionospheric perturbation, which occurs a few days before the EQ. Though there have been published several papers on the ionospheric plasma and wave characteristics before the Sichuan EQ on the basis of DEMETER satellite data [15]- [17] [36], the ground-based observation is definite to provide us with the detailed temporal evolution of different seismogenic phenomena when the number of stations is sufficient to form a network. We will compare our results on the lower ionosphere with those in the upper (F region) ionosphere based on the ground-based ionospheric measurements.…”
Section: Conclusion and Discussionmentioning
confidence: 99%